A cecropin-like antimicrobial peptide with anti-inflammatory activity from the black fly salivary glands. Issue 1 (December 2015) - Wu, Jing; Mu, Lixian; Zhuang, Li; Han, Yi; Liu, Tong; Li, Jun; Yang, Yuan; Yang, Hailong; Wei, Lin
Abstract Background Several antimicrobial peptides (AMPs) belonging to the cecropin family have been identified from the salivary glands of different black fly species, however, the immunological functions for these molecules were poorly understood. Methods A novel cecropin-like antimicrobial peptide (Siba Cec) was purified using reverse phase high-performance liquid chromatography (RP-HPLC) from the salivary glands of the black flySimulium bannaense . The amino acid sequence ofSiba Cec was determined by a combination method of automated Edman degradation and cDNA sequencing. The morphologic changes of Gram-negative bacteriaEscherichia coli treated withSiba Cec were assessed by scanning electron microscopy (SEM). Quantitative PCR (qPCR) was performed to analyze the mRNA expression of the inducible NO synthase (iNOS) and pro-inflammatory cytokines. Nitric oxide (NO) generation was examined using a Griess assay and the secretion of pro-inflammatory cytokines was determined by an enzyme-linked immunosorbent assay (ELISA). The activation of extracellular signal-regulated kinase (ERK), p38, and the nuclear translocation of nuclear factor-kappaB (NF-κB) were assessed by Western blotting analysis. Circular dichroism (CD) spectroscopy was performed to evaluate the secondary structure ofSiba Cec in solvent environment. Interaction ofSiba Cec with lipopolysaccharide (LPS) was studied using fluorescein isothiocyanate (FITC)- conjugated LPS aggregates. Neutralization of LPS bySiba Cec was assayed with the chromogenic limulus amebocyte lysate (LAL) test. qPCR was also used to analyze the expression ofSiba Cec mRNA in the salivary glands of insects after oral infection with the bacteriaE.coli. Results Siba Cec possessed potent antimicrobial activity against Gram-negative bacteria, and showed low cytotoxicity toward mammalian cells. SEM analysis indicated thatSiba Cec killed bacteria through the disruption of cell membrane integrity. Furthermore, Siba Cec significantly inhibited lipopolysaccharide (LPS)-induced production of NO and pro-inflammatory cytokines such as tumor necrosis factor-α (TNF-α), interferon-1β (IL-1β) and interferon-6 (IL-6) by blocking the activation of MAPKs and NF-κB signaling pathways. It mainly adopted an α-helix conformation in membrane-mimetic environments.Siba Cec could interact and neutralize LPS. Infection of black flies with bacteria caused an upregulation of the expression ofSiba Cec. Conclusions These results demonstrated that in addition to the bactericidal capacity, Siba Cec can function as immune regulator, inhibiting host secretion of inflammatory factors.